Mesoporous organosilicas with thiol functionalised pores: multifunctional dendrimers as sacrificial building block and template. Issue 42 (7th September 2022) - Laird, Mathilde; Herrmann, Niklas; Carcel, Carole; Trens, Philippe; Oliviero, Erwan; Toquer, Guillaume; Le Parc, Rozenn; Bantignies, Jean-Louis; Bartlett, John R.; Wong Chi Man, Michel
Abstract : Multifunctional PAMAM dendrimers are used as cleavable templates in silsesquioxane hybrids to generate tailored pores with functional pendant groups. Abstract : The synthesis of multifunctional poly(amidoamine) (PAMAM)-based dendrimers containing a cleavable disulfide linker within each arm of the dendrimer, together with condensable triethoxysilyl groups on the periphery of the dendrimer, is described. The dendrimers were mixed with 1, 4-bis(triethoxysilyl)benzene and subsequently transformed into silsesquioxane gels or periodic mesoporous organosilicas (PMOs) to generate materials with dendrimers covalently embedded within the interior of the silsesquioxane networks. Subsequent treatment of the gels with dithiothreitol enabled the core of the dendrimers to be selectively cleaved at the disulfide site, thus generating thiol functions localised within the pores. The effect of different dendrimer generations on the reactivity of the pendant thiol functions was probed by impregnation with gold salts, which were reduced to obtain gold nanoparticles within the pore networks of the gels and PMOs. The gels yielded polydisperse gold nanoparticles (2 to 70 nm) with dimensions modulated by the generation of the dendrimer, together with well-defined gold/thiolate clusters with Au⋯S distances of 2.3 Å. Such clusters were also observed in the PMO system, together with monodispersed gold nanoparticles with diameters comparable to that of the organised pores in the PMO. The role of surface functionalisation in controlling the formation of gold clusters and/or nanoparticles is discussed.